What are the implications of genetic variation on the control of Japanese encephalitis virus? - Bish, John L. (2024)
Japanese encephalitis virus (JEV) is a flavivirus endemic in southeast Asia, an area home to approximately 3 billion people. Infection with JEV can result in paralysis, epilepsy, and death. Currently JEV is well controlled owing to the introduction of several well-tolerated and highly efficacious vaccines.